The Nitrogen Balance of Indigeneous Yankasa Sheep fed a Basal Diet of Untreated Rice Straw Supplemented with Mineral Blocks - A. A. Mubi (Global Journal of Food and Agribusiness Management, 2020)
A research was conducted to determine the effects of two types of multinutrient block with or without molasses and a basal diet of rice straw on the performance of sheep. Three sheep were randomly allocated to three treatments group with a sheep per treatment in a metabolism cage the treatments were MNBM with basal diet, MNBW with basal diet and the Control. The metabolism trial was conducted to assess nitrogen balance in sheep fed a basal diet of rice straw and supplemented with MNBM and MNBW. Three Sheep were used for the trial, representing each treatment group. There was no significant (P>0.01) difference in the nitrogen retained between the supplemented group but differs (P<0.01) significantly with the control. The nitrogen retained were 5.78g/day, 24.96g/day and 25.87g/day for the control, MNBW and MNBM.There was no significant (P>0.01) difference between the supplemented groups, but differs (P<0.01) with the control group. The daily live weight change was – 0.02g/day, 0.39g/day and 0.40g/day for the control, MNBW and MNBM. The nutrient intake and digestibility by cattle was studied, the DMD of MNBM, MNBW and the control were 63.12%, 61.95% and 43.74%. CP digestibility was 77.11%, 75.87% and 42.27% for MNBM, MNBW and the control. The supplemented group had CF digestibility of 55.02%, 53.96% and 41.05% for MNBM, MNBW and the control.